The Relationship Between Coping Mechanisms and Stress Levels Among Adolescents Experiencing Parental Conflict at SMK Negeri 3 Bekasi City - Lestari, Cindy Arta; Nuryanti, Lisna; Pelawi, Arabta M Peraten (Althar Cendikia Education, 2025)
Stress is a state of physical and psychological tension that can disrupt both mental and physical health. According to the 2018 Basic Health Research (Riskesdas), approximately 19 million adolescents in Indonesia experienced mental health disorders. Stress is commonly defined as a process in which individuals evaluate an event as a threat, challenge, or danger. This study aimed to examine the relationship between coping mechanisms and stress levels among adolescents experiencing parental conflict at SMK Negeri 3 Bekasi City. A quantitative method was used to describe phenomena based on collected data. The study employed an analytical observational design with a cross-sectional approach to assess the relationship between independent and dependent variables. Data were collected through questionnaires distributed to 216 adolescents aged 15–18 years using a simple random sampling technique. The results of the Pearson Chi-Square test revealed a significant relationship between coping mechanisms and stress levels (p = 0.000). This finding indicates that coping mechanisms are strongly associated with adolescent stress in the context of parental conflict. These results may serve as a reference for educators, parents, and adolescents to better understand the importance of adaptive coping strategies in managing stress caused by family conflicts.